Composition, Biogenesis, and Role of Exosomes in Tumor Development - Leila Moeinzadeh; Iman Razeghian-Jahromi; Zeinab Zarei-Behjani; Zohreh Bagheri; Mahboobeh Razmkhah (Stem Cells International)
The role of exosomes and their mechanism of action at the tumor site have received increasing attention. These microvesicles are produced by a wide range of cells including mesenchymal stem cells (MSCs) and immune cells. In particular, tumor cells release remarkable amounts of exosomes which spread to distant organs through the blood and enhance the possibility of tumor metastasis. In spite of results on tumor promoting properties, there are reports demonstrating the tumor inhibiting effects of exosomes depending on the type of the tumor and cell source. This review aims to have a comprehensive appraisal on the biogenesis, composition, and isolation of exosomes and then highlights the current knowledge of their role in cancer progression or inhibition by special focusing on MSC’s exosomes (MSC-EXOs).